(untitled) (Lead City International Journal of Library, Information & Communication Sciences, 2024)
The management of information across organizations have shifted from the traditional methods to the digital space and this has been necessitated due to the infusion of Information and Communications Technology (ICT). This has become an important tool in the form of Electronic Records Management System (ERMS) for the day-to-day running of the office environment across organizations of which offices in tertiary institutions are not an exception. However, the reverse is the case in most public tertiary institutions in Nigeria which are still grabbling with the old order of managing its records. It is based on this premise that this study investigated the impact of using ERMS on the performance of administrative staff across the public polytechnics in Edo state, Nigeria. The Study adopted a positivist research paradigm and a quantitative research approach. Study population was 245 administrative staff while stratified sampling technique was used to select a sample of 74. Adapted Unified Theory of Acceptance and Use of Technology (UTAUT) research instrument was administered to users which revealed Administrative staff of public polytechnics in Edo State have accomplished a lot as a result of the use of ERMS. Computer/internet as well as technical assistants are available within the institutions to support administrative staff in the use of ERMS in case of any system malfunction or physical support. The study concluded that the availability of the facilities in these institutions and the ability of office managers to use the facilities had a great impact on their performance.